2015
DOI: 10.1182/blood.v126.23.5336.5336
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Myeloma Patients Are Vitamin D Deficient, Unrelated to Survival or Cytogenetics

Abstract: Introduction: Since a link between solar radiation, vitamin D production, and decreased colon cancer mortality was established in 1980, there has been increasing interest in vitamin D and cancer, suggesting that higher vitamin D levels improve overall survival, specifically in breast and colorectal cancer (Maalmi H et al, Eur J Canc, May-2014, PMID 24582912), but also in follicular lymphoma (Kelly JL, J Clin Onc, 1-May-2015, PMID 25823738). In myeloma, largest published series is from the Mayo Clinic reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A flow diagram of the article selection process is shown in Figure 1. 22 articles were excluded with the following reasons: (1) duplicate publications from overlapping cohort 47,48 , (2) insufficient data of primary endpoint [49][50][51][52][53][54][55][56][57][58][59][60] , and (3) transplantations including many non-malignancies or unidentified diseases [61][62][63][64][65][66][67][68] . The characteristics of each study are summarized in Table I.…”
Section: Study Selectionmentioning
confidence: 99%
“…A flow diagram of the article selection process is shown in Figure 1. 22 articles were excluded with the following reasons: (1) duplicate publications from overlapping cohort 47,48 , (2) insufficient data of primary endpoint [49][50][51][52][53][54][55][56][57][58][59][60] , and (3) transplantations including many non-malignancies or unidentified diseases [61][62][63][64][65][66][67][68] . The characteristics of each study are summarized in Table I.…”
Section: Study Selectionmentioning
confidence: 99%
“…Recent clinical studies have revealed a consistent and strong association between vitamin D status and tumor progression and survival in several solid tumor ( 7 ). Vitamin D deficiency is extremely common in patients with multiple myeloma (MM), however, data on the association between vitamin D status and clinical outcomes of newly diagnosed multiple myeloma (NDMM) are rather inconsistent ( 8 12 ). There was a study showing vitamin D deficiency in NDMM is unrelated to survival or cytogenetics ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in 2015, researchers reported that increased plasma cells in BM are correlated with VitD levels < 10 ng mL –1 [ 95 ]. In MM patients, most of whom lack vitamin D [ 96 ], this correlation was also valid in a long-term follow-up study, where the risk of progression, development of MBD and osteoporosis, and all-cause mortality was low in patients with adequate VitD levels (>75 nmol L −1 ) [ 97 ]. Moreover, in these patients, VitD analogues have been shown to promote cell cycle arrest [ 88 , 98 ].…”
Section: Vitamin D Status In Multiple Myelomamentioning
confidence: 94%